2021
DOI: 10.1123/jpah.2020-0516
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Frequent Light-Intensity Standing-Based Exercises That Interrupt 8 Hours of Prolonged Sitting on Postprandial Glucose in Stroke Survivors: A Dose-Escalation Trial

Abstract: Background: Interrupting prolonged sitting can attenuate postprandial glucose responses in overweight adults. The dose–response effect in stroke survivors is unknown. The authors investigated the effects of interrupting 8 hours of prolonged sitting with increasingly frequent bouts of light-intensity standing-based exercises on the postprandial glucose response in stroke survivors. Methods: Within-participant, laboratory-based, dose-escalation trial. Participants completed three 8-hour conditions: prolonged sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…While adjusting exercise bout duration and intensity is crucial to ensure tolerability for individuals based on their abilities and preferences, another essential factor to consider is the frequency of breaks, which appears to influence the post-meal glucose response. Several studies have shown a positive correlation between higher frequencies of activity breaks and greater improvements in postprandial glycemia in both healthy and diabetic populations [ 118 , 119 , 120 ]. While there is some variability in findings, with some studies indicating comparable effects regardless of break frequency, recent evidence suggests that more frequent breaks, such as exercising for 3 min every 15 min of sitting [ 120 ], or for 5 min every 30 min [ 121 ], might represent the optimal strategy for improving the post-meal glucose response.…”
Section: Activity Breaks: An Effective Exercise Modalitymentioning
confidence: 99%
“…While adjusting exercise bout duration and intensity is crucial to ensure tolerability for individuals based on their abilities and preferences, another essential factor to consider is the frequency of breaks, which appears to influence the post-meal glucose response. Several studies have shown a positive correlation between higher frequencies of activity breaks and greater improvements in postprandial glycemia in both healthy and diabetic populations [ 118 , 119 , 120 ]. While there is some variability in findings, with some studies indicating comparable effects regardless of break frequency, recent evidence suggests that more frequent breaks, such as exercising for 3 min every 15 min of sitting [ 120 ], or for 5 min every 30 min [ 121 ], might represent the optimal strategy for improving the post-meal glucose response.…”
Section: Activity Breaks: An Effective Exercise Modalitymentioning
confidence: 99%